Analysis of the Concept of Ta’awun in Hadith and Its Relevance to Social Resilience in Digital Media - Sakka, Abdul Rahman (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
Digital media, initially designed to strengthen social relationships, often becomes a source of division due to disinformation, polarisation, and cyberbullying. Using a qualitative approach through literature review and content analysis, this research examines hadiths related to ta’awun and how this concept can be adapted to address modern social challenges. The study finds that cooperation and mutual assistance within the concept of ta’awun possess unique characteristics defined by five essential criteria: being goodness-based, inclusive, certain, beneficial, and involving God. As a principle of helping one another for good, the concept of ta’awun holds significant potential for maintaining social resilience in digital media. Ta’awun not only strengthens solidarity but also promotes digital literacy and inclusivity within the digital space. Thus, ta’awun plays a crucial role in fostering social cohesion and countering the negative impacts of digital media.